A Gradient Weighted Moving Finite-Element Method with Polynomial Approximation of Any Degree. (24th August 2009) - Soheili, Ali R.; Naghipoor, J.; Ahmadian, S. A.
Abstract : A gradient weighted moving finite element method (GWMFE) based on piecewise polynomial of any degree is developed to solve time-dependent problems in two space dimensions. Numerical experiments are employed to test the accuracy and effciency of the proposed method with nonlinear Burger equation.